Observaciones ecológicas sobre la vegetación marina y terrestre de la Isla de los Estados (Tierra del Fuego, Argentina) - Kühnemann, Oscar (Ecosur, 2025)
A brief historical outline of the island is followed by Physiographical and Geological data compared with the “ Isla Grande Tierra del Fuego” . The author deais with the land ecosystem with commentaries about the principal ecological factors and their incidence upon the flora. Various communities are described and certain types of vegetal associations specially “ turbales” and the “ tundra”, are defined in their floristic and ecological characteristics,adding data about their presence in other argentine localities. A systematic list of the species of Bryophyta and vascular plants is added together, with a short reference about birds observed in location. In a sepárate chapter there is a description of the bentonic littoral ecosystem and the influence of the Malvinas coid stream together with the Coastal features and physical and Chemical factors. Within this ecosystem bionomical divisions of the Littoral system are determined and described. The ecological Supralittoral, Meso and Infralittoral levels, are determined and their limits set according to biological indicators. Taking into account the dominant species the foliowing communities are described: Macrocystis pyrifera forests; shrubs of DurviHea antárctica and Lessonia fuscescens; prairies of Rhodophyta; community of crustacean lichens; associations of Mytillus edulis, Au¡acomia ater “ cholga” , and belts of Cirripedia. Finally it is placed phytogeographycally within the Fueguine Province of the Atlantic Austral American Dominion, showing the biogeographic relationship with the “ Isla Grande de Tierra del Fuego” , “ Islas Malvinas” and “Georgias del Sur”.